Pollutant Remotion and Growth of Scenedesmus sp. on Wastewater from Tannery. A Comparison Between Free and Immobilized Cells (2018)
Tannery wastewater are a public health and ecosystem hazard, due to the high concentration of contaminants such as chrome, sulfides and others. One way to treat these waters is by the use of microorganisms such as microalgae due to their capacity to use the inorganic compounds, as well as to accumulate metals and other contaminant substances; ability that could be improve with cellular immobilization. In this paper, the growth and removal of nitrogen, phosphorus and chrome by the microalgae Scenedesmus sp. were evaluated, comparing the rates between free and immobilized cells in a Loofa matrix. In this way, a higher growth in the free cells was obtained, compared to the immobilized ones. However, there were no significant differences between removals of contaminants. In both cases, higher reductions than 90% for NO–3 , NH+4, PO34 and Chromium, as well as a significant reduction in BOD and COD (> 97%) were obtained, probably by a synergy effect between algae and bacteria presents in the culture. Finally, lipids in both cases were higher than 20%, showing that this biomass could present a high potential as a raw material for the generation of biodiesel.